Characterization of mussel (Perna canaliculus) haemocytes and their phagocytic activity across seasons. (8th June 2022) - Muznebin, Farhana; Alfaro, Andrea C.; Webb, Stephen C.; Merien, Fabrice
Abstract: Perna canaliculus is endemic to New Zealand and is the top shellfish export product. However, the growth of this industry is being adversely affected by summer mortality events. To assess these health threats, differential haemocyte counts (DHC) were performed on haemolymph smears stained with Giemsa, and in vitro phagocytosis activity assays were applied in P. canaliculus for several months covering three seasons (winter, spring and summer). A new optimized classification scheme was developed for P. canaliculus haemocytes where 55% eosinophilic and 27.2% basophilic granulocytes were identified. Eosinophilic granulocytes were classified as dense, semi and small semi, and these new categories were reported herein for the first time in this species. A new haemocyte type (mixed granulocytes), which contains both acidophilic and basophilic granules, is proposed for P. canaliculus . The phagocytosis percentages were significantly affected by incubation time, indicating an increase in zymosan particle uptake from 18.42 ± 1.7% after 30 min, 32.08 ± 3.1% after 60 min and 44.74 ± 3.5% (maximum) after 120 min of incubation. The lowest phagocytosis was observed in the winter season and the highest phagocytosis in summer. This study findings provide a better understanding of the immune function of P. canaliculus haemocytes and serve as a reference for further investigations on the impacts of seasonal variations on haemocyte activity and phagocytosis.